Study of effectiveness of management by objectives among service units at MISC Bhd / Siti Nor Hajar Rusmi - Rusmi, Siti Nor Hajar (2011)
The effectiveness means to which degrees that we can achieve on objectives set. In order to achieve this highest and the best degrees, a good leadership and management should be emphasis also the comprehensive criteria. Without having this, the whole process of performance management may be collapse or disorganize and leaders should play an important roles in order to control the process. This research is to investigate what are the most factors that may contribute towards the effectiveness. At the end of this research it will determine whether Management by Objectives factors such as leadership, criteria and job satisfaction will affect the effectiveness at MISC or not. By using the entire 60 questionnaires, the finding highlighted on the three of the effectiveness as mentioned. Therefore, in order to determine the relationship between Management by Objectives Factors and The Effectiveness, a Likert-type scale has been develop and tested. Therefore in this research, the researcher tries to identify the most influential factor and the relationship between dependant and independent variables .Based on the result it shows that the selected factors are agreeing by respondent and it has good relationship.